1998
DOI: 10.1111/j.1540-6288.1998.tb01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Stock Prices and the Secondary Dissemination of Information: The Wall Street Journal's “Insider Trading Spotlight”Column

Abstract: In this paper we test whether a secondary dissemination of information affects stock prices. We examine stock price reactions to the publication of the "Insider Trading Spotlight" (ITS) column in the Wall Street Journal (WSJ). Since insider trades reported in the ITS column are initially disclosed to the public when insiders' reports are filed with the Securities and Exchange Commission (SEC), the information contained in the WSJ is a secondary dissemination. Around the WSJ publication day, we find significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 17 publications
4
46
0
Order By: Relevance
“…Shortly afterwards, the information is published in the Wall Street Journal (WSJ) and other publications. Chang and Suk (1998) find that there is a significant share price reaction even after the announcement in the WSJ which suggests that the SEC online report is only read by a small number of investors whereas the WSJ is read by a larger number of investors. 7 This implies that not only is the reporting process in the US slower, but it also takes time for the information contained in the insider trades to be reflected in the share price.…”
Section: In the Us Insider Trading Is Regulated By The Securities Exmentioning
confidence: 84%
See 2 more Smart Citations
“…Shortly afterwards, the information is published in the Wall Street Journal (WSJ) and other publications. Chang and Suk (1998) find that there is a significant share price reaction even after the announcement in the WSJ which suggests that the SEC online report is only read by a small number of investors whereas the WSJ is read by a larger number of investors. 7 This implies that not only is the reporting process in the US slower, but it also takes time for the information contained in the insider trades to be reflected in the share price.…”
Section: In the Us Insider Trading Is Regulated By The Securities Exmentioning
confidence: 84%
“…Chang and Suk (1998) write that trades normally appear in the online report 2 See Pope et al (1990, p.371). 3 In exceptional circumstances where it is the only reasonable course of action available to a director, clearance may be given to the director to sell (but not to purchase) when he would otherwise be prohibited from doing so.…”
Section: In the Us Insider Trading Is Regulated By The Securities Exmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by a host of papers documenting that insider trades, and purchases in particular, convey information to the market (e.g., Seyhun (1986) and Chang and Suk (1998) for the US; Fidrmuc et al (2006) and Friederich et al (2002) for the UK). The US and many other countries have adopted regulations that require corporate insiders to report their trades.…”
mentioning
confidence: 93%
“…The authors show that information is reflected more rapidly in prices when insiders have to disclose their trades. Several empirical papers (e.g., Chang and Suk (1998), Betzer and Theissen (2009)) have shown that share price reactions occur on both the trading and reporting dates. Thus, without the report the market is unable to infer the full information content of the trade, which implies that market prices are distorted in the period between the trading and reporting dates.…”
mentioning
confidence: 99%